THE HANDBOOK OF ENVIRONMENTAL EDUCATION. (Authors: Joy Palmer & Philip Neal) - Oliver, Gordon (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1995)
Joy Palmer & Philip Neal. THE HANDBOOK OF ENVIRONMENTAL EDUCATION. London & New York: Routledge. 1994. 267 pp. $24.95 (paper). ISBN 0-4115-09314-7.